Focusing on the coach's eye; towards a working model of coach decision-making in talent selection. (September 2021) - Lath, Franziska; Koopmann, Till; Faber, Irene; Baker, Joseph; Schorer, Jörg
Abstract: Talent selection has become an integral part of many nations' athlete development systems. In this context, a coach often serves as a decision-maker, selecting or deselecting athletes based on their intuition, a phenomenon that has generally come to be referred to as "coach's eye". However, there is no consistent operational definition of this term. To this end, we reviewed prior work using the term "coach's eye" as reflecting the process of coaches assessing and selecting athletes during talent selection scenarios. Based on previous research, four main characteristics of the coaches' eye were identified: intuitive, subjective, experience-based and holistic. Results emphasize the underlying mechanisms of the coach's eye are still unknown and links to theoretical models are missing. In the final section of this paper, we describe a model from decision-making research, the iCodes model (integrated coherence-based decision and search model) by Jekel, Glöckner, and Bröder (2018), and apply it to talent selection scenarios. We believe this model provides a useful starting point for investigating the decision process and the underlying mechanisms of the coach's eye. Highlights: A definition for the term "coach's eye" is formulated through a qualitative review process. An overview about the actual research state of the "coach's eye" is given based on the definition. Coach's eye is linked to a model (iCodes) and provide theory guided research.